Molecular and functional characterization of a Trypanosoma cruzi nuclear adenylate kinase isoform. - María de los Milagros Cámara; León A Bouvier; Gaspar E Canepa; Mariana R Miranda; Claudio A Pereira (Public Library of Science (PLoS), 2013)
Trypanosoma cruzi, the etiological agent of Chagas' disease, is an early divergent eukaryote in which control of gene expression relies mainly in post-transcriptional mechanisms. Transcription levels are globally up and down regulated during the transition between proliferating and non-proliferating life-cycle stages. In this work we characterized a nuclear adenylate kinase isoform (TcADKn) that is involved in ribosome biogenesis. Nuclear adenylate kinases have been recently described in a few organisms, being all related to RNA metabolism. Depending on active transcription and translation, TcADKn localizes in the nucleolus or the cytoplasm. A non-canonical nuclear localization signal was mapped towards the N-terminal of the protein, being the phosphate-binding loop essential for its localization. In addition, TcADKn nuclear exportation depends on the nuclear exportation adapter CRM1. TcADKn nuclear shuttling is governed by nutrient availability, oxidative stress and by the equivalent in T. cruzi of the mammalian TOR (Target of Rapamycin) pathway. One of the biological functions of TcADKn is ribosomal 18S RNA processing by direct interaction with ribosomal protein TcRps14. Finally, TcADKn expression is regulated by its 3' UTR mRNA. Depending on extracellular conditions, cells modulate protein translation rates regulating ribosome biogenesis and nuclear adenylate kinases are probably key components in these processes.